Knock-Out of ACBD3 Leads to Dispersed Golgi Structure, but Unaffected Mitochondrial Functions in HEK293 and HeLa Cells - Daňhelovská, Tereza; Zdražilová, Lucie; Štufková, Hana; Vanišová, Marie; Volfová, Nikol; Křížová, Jana; Kuda, Ondřej; Sládková, Jana; Tesařová, Markéta (International journal of molecular sciences, 2021)
The Acyl-CoA-binding domain-containing protein (ACBD3) plays multiple roles across the cell. Although generally associated with the Golgi apparatus, it operates also in mitochondria. In steroidogenic cells, ACBD3 is an important part of a multiprotein complex transporting cholesterol into mitochondria. Balance in mitochondrial cholesterol is essential for proper mitochondrial protein biosynthesis, among others. We generated ACBD3 knock-out (ACBD3-KO) HEK293 and HeLa cells and characterized the impact of protein absence on mitochondria, Golgi, and lipid profile. In ACBD3-KO cells, cholesterol level and mitochondrial structure and functions are not altered, demonstrating that an alternative pathway of cholesterol transport into mitochondria exists. However, ACBD3-KO cells exhibit enlarged Golgi area with absence of stacks and ribbon-like formation, confirming the importance of ACBD3 in Golgi stacking. The glycosylation of the LAMP2 glycoprotein was not affected by the altered Golgi structure. Moreover, decreased sphingomyelins together with normal ceramides and sphingomyelin synthase activity reveal the importance of ACBD3 in ceramide transport from ER to Golgi.
Keywords: HEK293 buňky; HeLa Cells; adaptorové proteiny signální transdukční; membránový protein 2 asociovaný s lyzozomy; mitochondrie; Adaptor Proteins, Signal Transducing; knock-out; Golgi Apparatus; Lysosomal-Associated Membrane Protein 2; signální transdukce; Humans; Golgiho aparát; OXPHOS; transferasy pro jiné substituované fosfátové skupiny; Golgi; Mitochondria; Signal Transduction; Glycosylation; ceramidy; glykosylace; lidé; HEK293 Cells; Membrane Proteins; mitochondria; Ceramides; Transferases (Other Substituted Phosphate Groups); Cholesterol; membránové proteiny; biologický transport; Biological Transport; HeLa buňky; ACBD3; cholesterol